Social media metrics : how to measure and optimize your marketing investment - Sterne, Jim, 1955- (New rules of social media series., 2010)
A guide devoted exclusively to social media metrics. Whether you are selling online, through a direct sales force, or via distribution channels, what customers are saying about you online is now more important than your advertising. Social media is no longer a curiosity on the horizon but a significant part of your marketing mix. While other books explain why social media is critical and how to go about participating, Social Media Metrics focuses on measuring the success of your social media marketing efforts.